Constraints to gene flow increase the risk of genome erosion in the Ngorongoro Crater lion population - Nicolas Dussex; Ingela Jansson; Tom van der Valk; Craig Packer; Anita Norman; Bernard M. Kissui; Ernest E. Mjingo; Göran Spong (Communications Biology)
Abstract Small, isolated populations are at greater risk of genome erosion than larger populations. Successful conservation efforts may lead to demographic recovery and mitigate the negative genetic effects of bottlenecks. However, constrained gene flow can hamper genomic recovery. Here, we use population genomic analyses and forward simulations to assess the genomic impacts of near extinction in the isolated Ngorongoro Crater lion (Panthera leo) sub-population. We show that 200 years of quasi-isolation and the recent epizootic in 1962 resulted in a two-fold increase in inbreeding and an excess in the frequency of highly deleterious mutations relative to other populations of the Greater Serengeti. There was little evidence for purging of genetic load. Furthermore, forward simulations indicate that higher gene flow from outside of the Crater is needed to prevent future genomic erosion in the population, with a minimum of one to five effective male migrants per decade required to reduce the risk of long-term inbreeding depression and reduction in genetic diversity. Our results suggest that in spite of a rapid post-epizootic demographic recovery since the 1970s, continued isolation of the population driven by habitat fragmentation and potentially male territoriality, exacerbate the effects of genome erosion.